2013
DOI: 10.1088/1367-2630/15/11/115005
|View full text |Cite
|
Sign up to set email alerts
|

Berry phases of quantum trajectories of optically excited electron–hole pairs in semiconductors under strong terahertz fields

Abstract: The quantum evolution of particles under strong fields can be essentially captured by a small number of quantum trajectories that satisfy the stationary phase condition of the Dirac-Feynmann path integral. The quantum trajectories are a key concept in understanding extreme nonlinear optical phenomena, such as high-order harmonic generation (HHG) and highorder terahertz sideband generation (HSG). In contrast to HHG in atoms and molecules, HSG in semiconductors can have interesting effects due to nontrivial 'vac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…A fundamental difference between HHG and HSG is that the electron-hole pair in semiconductors can have nontrivial Bloch states [1]. As a result, when the electron (or hole) is driven by the THz field in the conduction (or valence) band, not only does the quasi-momentum k change [8], but also the Bloch wavefunction evolves with k. Since the THz frequency is much smaller than the band gaps of semiconductors, the evolution is adiabatic (i.e.…”
Section: Abstract: Faraday Rotation Berry Phase Bilayer Graphene Tmentioning
confidence: 99%
See 4 more Smart Citations
“…A fundamental difference between HHG and HSG is that the electron-hole pair in semiconductors can have nontrivial Bloch states [1]. As a result, when the electron (or hole) is driven by the THz field in the conduction (or valence) band, not only does the quasi-momentum k change [8], but also the Bloch wavefunction evolves with k. Since the THz frequency is much smaller than the band gaps of semiconductors, the evolution is adiabatic (i.e.…”
Section: Abstract: Faraday Rotation Berry Phase Bilayer Graphene Tmentioning
confidence: 99%
“…In [1], we studied the Berry phases of quantum trajectories in monolayer MoS 2 with a band gap in the visible wavelength regime. We found that the optical emission delayed by integer multiples of the THz period after the pulse excitation acquired a Faraday rotation, and the rotation angle was exactly the Berry phase of the quantum trajectory (∼0.01 rad for a THz field with frequency 1 THz and strength 8 kV cm −1 ).…”
Section: Abstract: Faraday Rotation Berry Phase Bilayer Graphene Tmentioning
confidence: 99%
See 3 more Smart Citations